The Zeebrugge ferry disaster: elements of a communication and information processes scenario - Pijnenburg, Bert (Contemporary crises, 1990)
On Friday 6 March, 1987, at approximately 19:30 the Herald of Free Enterprise ferry boat capsized just outside the Belgian harbour of Zeebrugge. Almost 200 people died as the ship sank very quickly. This article examines the emergency operations that followed the disaster from the perspective of information and communication dynamics. Five specific aspects are thus analyzed in greater detail and elements of an alternative scenario are suggested for each of them: the initial alert and the subsequent mobilization of the emergency services; the informationhandling performance of the crisis center; interorganizational communication between disasterrelief agencies; external communication to survivors, families and next of kin; the management of the mass media. It is concluded that, when examining the crisis management operations more closely, the alleged success of Belgian disaster relief operations at Zeebrugge appears in many respects something of a myth.The paper is commented on by John P. Heck, Head of Civil Defense at the Dutch Ministry of the Interior.